Imperfection insensitive thin cylindrical shells for next generation wind turbine towers. (September 2020) - Yadav, Kshitij Kumar; Gerasimidis, Simos
Abstract: Conventionally, wind turbine towers are made of thin steel circular cylindrical shells due to the structural efficiency and the ease of construction. But, thin cylindrical shells are highly sensitive to imperfections, and the presence of even slight imperfections reduces their capacity severely. Imperfections are always present in the cylinders, and thus the design methods have the provisions to accommodate the presence of imperfections. As a result, the current practices for designing wind turbine towers that are made by thin circular cylinders are conservative. These conservative design methods have long been an obstacle for cost effective wind turbines, whose demands have been increased recently due to the widespread awareness of the clean source of wind energy. Wavy wind turbine towers are proposed in this study to avoid these roadblocks towards more efficient tall wind turbine towers. The waviness of the cross-section reduces the slenderness ( R / t ) of the towers significantly; consequently, the sensitivity of the towers to imperfections is reduced drastically. In addition, the waviness of the cross-sections works as stiffeners which also results to the reduction of imperfection sensitivity. Imperfection sensitivity of wavy cylindrical shells has been evaluated in the past along with highly promising results. However, no attempt has been made to evaluate the effectiveness of the wavy cylinders in a real application. In this study, the sensitivity of the proposed wavy wind turbine towers to imperfections is assessed. It is found that the sensitivity of the wavy towers is exceptionally small compared to that of the circular towers. Graphical abstract: Unlabelled Image Highlights: Wavy wind turbine towers are proposed for making efficient and tall wind turbine towers. The waviness of the cross-section reduces the slenderness (R/t); consequently, the sensitivity to imperfections is reduced. Two kinds of geometric imperfections, Modal shape and Dimple-like are studied. It is found that the sensitivity of the wavy towers is exceptionally small compared to that of the circular towers.